Results of trawl survays of pacific salmon juviniles in the Bering and Okhotsk Seas in autumn 2021 - A. N. Starovoitov; S. S. Ponomarev; D. N. Chulchekov (Известия ТИНРО, 2022)
The results of trawl surveys at western part of Bering Sea and Okhotsk Sea at the R\V «TINRO» and R/V «Professor Kaganovskii» in the fall 2021 are analyzed. These studies provide data on spatial distribution, abundance and biomass of fishes, cephalopods and jellyfishes in the epipelagic layer of the Bering and Okhotsk Seas. The analysis of the contemporary status of epipelagic nekton communities of the Bering and Okhotsk Seas is provided. Quantitative distribution and biological state of juveniles of pink salmon in the autumn season is reviewed in full detail.